Anthelmintic control strategies for equines strongylidosis - Cernea, M. (Medicamentul Veterinar)
Equine strongylidosis study is a world - wide highly important topic due to the serious consequences this disease can induce both by simptomathology and by decreasing physical capacity of animals. Strongyls presence may modify behavior, fertility, physical condition, organism development through maturity, decreases resistance to other phatogenous agents and may even become the cause of death. Due to extension and prejudices these diseases can inflict, diagnosis of parasite invasions has to be made even for those with sub-clinical evolution. This diagnosis must be followed by exact identification of the etiological agent involved as well as its genetical, biological and ecological characteristic, and also the possible resistance to specific medication, taking in to account the selection of certain antiparasitary medicine with enhanced efficacy. Regardless of the medicine or dehelmintization programme used, systematic investigation of resistant helminthes populations must constitute a sine qua non condition in modern parasitology.